Two new species of Japanagallia Ishihara, 1955 from China (Hemiptera: Cicadellidae: Megophthalminae) - Zhang, Bin (Zootaxa, 2010)
Two new leafhopper species of the genus Japanagallia, J. spinosa sp. nov. and J. lamellata sp. nov. are described and illustrated from southern China. A redescription of the genus is provided and a key to Chinese species of the genus is also given.